Rapidly fatal myeloproliferative disorders in mice with deletion of Casitas B-cell lymphoma (Cbl) and Cbl-b in hematopoietic stem cells - Naramura, Mayumi (National Academy of Sciences, 2010)
Casitas B-cell lymphoma (Cbl)-family E3 ubiquitin ligases are negative regulators of tyrosine kinase signaling. Recent work has revealed a critical role of Cbl in the maintenance of hematopoietic stem cell (HSC) homeostasis, and mutations in CBL have been identified in myeloid malignancies. Here we show that, in contrast to Cbl or Cbl-b single-deficient mice, concurrent loss of Cbl and Cbl-b in the HSC compartment leads to an early-onset lethal myeloproliferative disease in mice. Cbl, Cbl-b double-deficient bone marrow cells are hypersensitive to cytokines, and show altered biochemical response to thrombopoietin. Thus, Cbl and Cbl-b play redundant but essential roles in HSC regulation, whose breakdown leads to hematological abnormalities that phenocopy crucial aspects of mutant Cbl-driven human myeloid malignancies.